2019
DOI: 10.1002/ijc.32217
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA mutations in gastric washes from gastric adenocarcinoma patients: Possible implications for liquid biopsies and patient follow‐up

Abstract: Whereas cancer patients have benefited from liquid biopsies, the scenario for gastric adenocarcinoma (GAC) is still dismal. We used next‐generation deep sequencing of TP53—a highly mutated and informative gene in GAC—to assess mutations in tumor biopsies, plasma (PL) and stomach fluids (gastric wash—GW). We evaluated their potential to reveal tumor‐derived mutations, useful for monitoring mutational dynamics at diagnosis, progression and treatment. Exon‐capture libraries were constructed from 46 patients inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…As one of the diseases that seriously endangers human health, GC has caused nearly 780,000 deaths worldwide in 2018, according to recent statistics 1 . The majority of GC patients are diagnosed at an advanced stage and, consequently, have already lost their best chances of treatment 28 . A vital reason for this phenomenon is that GC has a powerful capacity to generate new blood vessels, leading to continuous proliferation, metastasis, and rapid deterioration 29 .…”
Section: Discussionmentioning
confidence: 99%
“…As one of the diseases that seriously endangers human health, GC has caused nearly 780,000 deaths worldwide in 2018, according to recent statistics 1 . The majority of GC patients are diagnosed at an advanced stage and, consequently, have already lost their best chances of treatment 28 . A vital reason for this phenomenon is that GC has a powerful capacity to generate new blood vessels, leading to continuous proliferation, metastasis, and rapid deterioration 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides blood, other biofluids, such as urine [7,23,28,37,39,47,52], cerebrospinal fluid (CSF) [60], and gastric washes [54], have been shown to harbor ctDNA. Depending on the type of cancer, tumors might more closely contact with different fluids that, consequently, might contain higher ctDNA concentrations than blood [23].…”
Section: Liquid Biopsies For Diagnosis and Tumor Profilingmentioning
confidence: 99%
“…The results showed that tp53 mutations were identified in 15/46 biopsies (32.6%), 7/46 gastric wash - (15.2%) and 6/46 plasma samples (13%). The authors suggested that gastric wash could be useful to detect DNA alterations using a comprehensive gene-panel designed for GC diagnosis[47].…”
Section: Oncogenes/tumor Suppressors In Gcmentioning
confidence: 99%